2012
DOI: 10.1063/1.4756696
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of free-standing versus matrix-embedded oxide-passivated silicon nanocrystals: The role of matrix-induced strain

Abstract: On the method of photoluminescence spectral intensity ratio imaging of silicon bricks: Advances and limitations J. Appl. Phys. 112, 063116 (2012) Measurement of net dopant concentration via dynamic photoluminescence J. Appl. Phys. 112, 063704 (2012) Luminescence and deep-level transient spectroscopy of grown dislocation-rich Si layers AIP Advances 2, 032152 (2012) The role of excess minority carriers in light induced degradation examined by photoluminescence imaging J. Appl. Phys. 112, 033703 (2012) Effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 61 publications
8
50
0
Order By: Relevance
“…The optimum conditions when both effects are minimized, namely, a lower presence of free carriers and low enough matrix stress, are reached at t SiO2 = 2 nm. Both hypotheses are plausible in the frame where the NC interaction does not cause a loss of exciton confinement within the NCs (the nanostructure morphology is not varied [33]), which is corroborated by identical Raman spectra (see figure 2(a)) and the constant EL peak position in the spectra shown in figure 4(a). Other competing effects may take place regarding the barrier thickness modification that are related to the NC excitation, which requires a further analysis on the correlation between charge injection within the SLs and the luminescence yielded by the structures, as will be treated in the following section.…”
Section: Carrier Recombination Dynamicssupporting
confidence: 58%
See 1 more Smart Citation
“…The optimum conditions when both effects are minimized, namely, a lower presence of free carriers and low enough matrix stress, are reached at t SiO2 = 2 nm. Both hypotheses are plausible in the frame where the NC interaction does not cause a loss of exciton confinement within the NCs (the nanostructure morphology is not varied [33]), which is corroborated by identical Raman spectra (see figure 2(a)) and the constant EL peak position in the spectra shown in figure 4(a). Other competing effects may take place regarding the barrier thickness modification that are related to the NC excitation, which requires a further analysis on the correlation between charge injection within the SLs and the luminescence yielded by the structures, as will be treated in the following section.…”
Section: Carrier Recombination Dynamicssupporting
confidence: 58%
“…In the opposite case, i.e. for thicker barriers, the higher stress generated by the larger SiO 2 presence surrounding the NCs [11,33] may give rise to an instability of the confined excitons, thus reducing the recombination time. The optimum conditions when both effects are minimized, namely, a lower presence of free carriers and low enough matrix stress, are reached at t SiO2 = 2 nm.…”
Section: Carrier Recombination Dynamicsmentioning
confidence: 99%
“…Godefroo and co-authors, using PL measurements under high magnetic fields, showed that the optical emission of as-crystallized SiO x /SiO 2 superlattices may be related to defects, whereas it becomes entirely originated by excitonic quantum confinement (QC) after H passivation [7]. Matrix-induced strain has also been shown to play an important role in the optical emission of matrix-embedded Si NCs relative to free-standing material [9].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of much effort to investigate the optical properties of nanosized Si, the actual origin of its strong PL signal is still under debate [7][8][9][10]. While many experimental works point toward strong luminescence due to quantum-confined excitons in Si nanostructures fabricated with different methods [8,[11][12][13][14], others suggest that the PL emission arises from highly localized surface states [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that strain can modify the electronic structure of semiconductor nanocrystals and consequently their PL spectra [15,21,22]. Since we know from our x-ray diffraction measurement that Li-doped SiNCs have an expanded lattice, i.e., tensile strain is present in these nanocrystals, we can expect that the PL spectra will be influenced by this tensile strain.…”
Section: Discussionmentioning
confidence: 99%